An??lise da viabilidade de utiliza????o da saliva como fonte de material biol??gico para o estudo de biomarcadores na Doen??a Pulmonar Obstrutiva Cr??nica (DPOC) - Santos, Alecsandra Aparecida dos (2008)
The increased expression of matrix metalloproteinases (MMPs) is considered to be a key factor in the development of COPD. We performed this study to quantify the expression of MMP-2 and MMP-9 in saliva of COPD patients and healthy controls, and to evaluate feasibility of saliva compounds as a biological material source for the study of biomarkers in COPD. Methods: COPD patients (n=16) and healthy controls (n=9) were selected. In the both group spirometry test was performed and saliva samples were obtained from each subject. The saliva levels of MMP-2 and MMP-9 were determined by Western Blot. Results: MMP-2 and MMP-9 were significantly higher in COPD patients than in control subjects. MMP-2 concentration was correlated negatively with forced expiatory volume in one second (FEV1) (r= -0,582; p= 0,014) in COPD patients. Conclusion: The current findings open new perspectives to study specific biomarkers in saliva to predict and monitor airway obstruction in COPD patients